Topographic correspondence between retinotopic and whisker somatosensory map in mouse higher visual area and its development - Matsumoto, Hanaka; Murakami, Tomonari; Ohki, Kenichi (Frontiers in Neural Circuits, 2025)
Aligning the topography maps of different sensory modalities in the brain is considered to be important for the unified perception of multiple sensory modalities. In mice, the superior colliculus receives both visual and whisker-related somatosensory information with the topographical correspondence between retinotopy and somatotopy. However, it remains unclear whether topographical correspondence between retinotopy and whisker somatotopy exists in the higher association cortex, and if so, how this functional organization is formed during development. Here, we conducted wide-field calcium imaging and revealed retinotopic and somatotopic correspondence in the rostrolateral area (RL), one of the higher visual areas. The retinotopic map demonstrates that RL is divided into two distinct subregions, anterior and posterior parts of RL (RLa and RLp). We further found a rough topographic correspondence between retinotopy and whisker somatotopy only in RLa, but not in RLp, Lastly, to test whether this topographic correspondence exists before eye-opening, we performed functional connectivity analysis of spontaneous cortical activity recorded from developing mice. We discovered that the topographical correspondence between retinotopy-like and somatotopy-like structures in RLa already existed before eye-opening, on postnatal day 10–11. Because spatially corresponding multisensory inputs are likely quite weak before eye-opening, these results in developing mice suggest that the initial formation of topographic correspondence between retinotopy and whisker somatotopy in the higher association cortex does not depend on spatially corresponding multisensory input experiences.